Optimal Contract Choice in Sustainable Tourism Supply Chain When Environmental Consumers Exist - Fei Du; Dejun Zou; Jianping Hu (SAGE Open)
With the rapid development of online tourism, a significant number of sustainable hotels have established cooperation with online travel agencies (OTAs) for room sales. This study introduces an analytical framework for a sustainable supply chain model, involving a sustainable hotel and an OTA. Utilizing Stackelberg game theory, we investigate the two parties’ decision-making processes as they consider contracts for reselling, cost sharing, and revenue sharing. Our analysis reveals that cost sharing and revenue sharing contracts are more effective in motivating the hotel to implement environmental effort than reselling contract. Furthermore, our findings indicate that revenue sharing contract performs best in alleviating double marginalization within the sustainable supply chain by lowering the price of sustainable products. Additionally, revenue sharing contract empowers the hotel and OTA to maximize their profits, making it an optimal choice for the two parties to achieve a win-win outcome.